Analisis Motivasi Lulusan Pelaut Menjadi Tenaga Pendidik pada Program Diploma Pelayaran di Universitas Hang Tuah Surabaya - Purwiyanto, Didik (Universitas Hang Tuah, 2020)
The purpose of this study is to measure the motivation of graduates of seafarers to become lectures in the Program Diploma Pelayaran-Universitas Hang Tuah Surabaya (PDP-UHT) using professional training variables, professional recognition, job market considerations, financial awards, work environment and policy and administration, to get a true picture of existing and ongoing conditions.As well as measuring factors to be educators in PDP-UHT related regulations from the Kementerian Pendidikan dan Kebudayaan (Dirjen Dikti) and Kementrian Perhubungan Laut (Dirjen Hubla). Career selection planning is a very important thing to achieve success in career. The plan includes consideration of some of the dominant factors in career selection. Graduates of PDP-UHT seafarers in choosing their career will have various considerations. On the other hand the shipping university in this case is the PDP-UHT has two main institutions that must be obeyed, namely the Dirjen Dikti and Dirjen Hublaabout the implementation of the program related to the fulfillment of the minimum number of lecture for each course is to meet the qualifications of both institutions.